Symmetrical and Asymmetrical Thiophene-Coumarin-Based Organic Semiconductors - Altınışık, Sinem; Özdemir, Mücahit; Kortun, Arzu; Zorlu, Yunus; Yalçın, Bahattin; Köksoy, Baybars; Koyuncu, Sermet (American Chemical Society, 2023)
Organic semiconductors are a valuable material class for optoelectronic applications due to their electronic and optical properties. Four new symmetric and asymmetric thiophene-coumarin derivatives were designed and synthesized via Pd-catalyzed Suzuki and Stille Cross-Coupling reactions. Single crystals of all synthesized thiophene-coumarin derivatives were obtained, and π···π interactions were observed among them. The π···π interactions were supported by UV-vis, transmission electron microscopy, and atomic force microscopy analyses. The photophysical and electrochemical properties of the coumarins were investigated and supported by density functional theory studies. Fluorescence quantum yields were recorded between 36 and 66%. Moreover, mega Stokes shifts (175 nm or 8920 cm) were observed in these new chromophore dyes. The emission and absorption colors of the thiophene-coumarin compounds differed between their solution and film forms. Electrochemically, the highest occupied molecular orbital levels of the coumarins increased with the 3,4-ethylenedioxythiophene group, leading to a narrowing of the band gap, while the phenyl bridge weakened the donor-acceptor interaction, expanding the band gap.
Keywords: Absorption; Aromatic compounds; Electrical conductivity; Molecular interactions; Thiophenes